SOCIAL MEDIA ANALYTICS IN CONTEMPORARY ART PROMOTION - Bhatt, Pooja; Chaudhary, Swati; Joglekar, Shweta; Vidyashree S M; Pandey, Sakshi; Kaur, Ashmeet (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Social media is a new phenomenon in the marketing and distribution of modern art in the digital era. Instagram, X (previously Twitter), Tik Tok and Facebook have transformed the experience of artist, gallery and institution interaction with the global audience. This research examines how the social media analytics support modern art promotion with a particular focus on how data-driven insights can be used to make creative and marketing choices. Knowing the audience behaviour, sentiment and engagement metrics, artists and curators are able to optimise on what they communicate, get maximum visibility and judge the campaign success in real time. In the article, the current literature on the topic of digital art marketing is reviewed and the way analytics tools (Meta Insights and Google Analytics) can be utilized to monitor the performance in terms of the primary metrics, such as impressions, reach, shares, and click-through rates. The paper discusses the place of analytics in fuelling artistic outreach and commercial success by employing a mixed methods research design incorporating content analysis, surveys and interviews to examine the connection between this concept and the other components of organizational strategy. Results indicate that the effective application of analytics is not only a better way to engage, but also attains inclusive and sustainable digital art communities. Yet, there are still difficulties associated with the interpretation of data, algorithmic bias, and other ethical aspects of personal data use. The conclusion of the paper is that the incorporation of social media analytics into art marketing systems can help artists and institutions to make decisions based on information, meet the demands of the audience, and survive in the changing digital landscape of modern art advertising.